Food behavior and mental and emotional health in Emergency Remote Teaching (ERE) of higher education servers and students in Brazil during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
Objective: To investigate in the literature the changes in eating behavior and mental and emotional health in higher education servers and students in Brazil during Emergency Remote Teaching (ERE) established during the COVID-19 pandemic. Method: This is an integrative qualitative literature review. The research was constituted, respectively, in six stages, they are: 1 - elaboration of the guiding question of the research, 2 - definition of the databases to be used, 3 - Formulation of the inclusion and exclusion criteria of the articles in the research, 4 - Definition and collection of data, 5 - Analysis of included studies and 6 - Presentation of the results of the included and analyzed data. The search for articles was carried out through the Virtual Health Library (VHL) (BIREME) and capes journals, using descriptors (Portuguese and English). Results: database searches retrieved 736 articles, however, after reading, the final sample consisted of 17 articles that met the eligibility criteria. Scientific evidence shows negative impacts on the mental and emotional health of university students and professors, with regard to eating behavior, most negative changes were identified, represented by increased intake of ultra-processed foods, increased hours eating and seeking of emotional comfort through food. Conclusion: the pandemic context reflected, for the most part, negatively, on the mental and emotional health of the studied groups.